(untitled) (European Journal of Marketing and Economics, 2026)
This article underscores the critical role of the legal framework in facilitating effective marketing activities, addressing emergent issues, and safeguarding consumer interests in Georgia. It traces the development of Georgia’s business legal framework, with particular emphasis on legislative efforts subsequent to the signing and implementation of the Association Agreement with the European Union. The paper specifically analyzes key Georgian statutes pertinent to consumer rights protection, including the Code of Food Safety and Free Circulation, the Code of Food/Animal Fodder Safety, Veterinary and Plants Protection, the Law on Advertising, and various Technical Regulations concerning food product labeling and consumer information. A notable legislative gap is identified: the 2012 suspension of the Georgian Law on Protection of Consumers’ Rights, despite a prepared and published draft law, remains unaddressed. Based on this legal analysis, the author concludes that while effective legislation generally protects consumer rights in Georgia, the crucial challenge lies in enforcement. To this end, the article highlights the government’s 2015 resolution on Food/Animal Fodder Safety State Control Rule, which mandates state oversight of relevant businesses to protect consumers. The ongoing process of refining Georgia’s marketing-related legal foundation is also discussed.